Exploring urban paradigms tackling COVID-19 in blogs communities: The case of SDG 11: استكشاف تصدي النماذج الفكرية الحضرية لـكوفيد-19 في مجتمعات المدونات: حالة الهدف 11 للتنمية المستدامة - Hisham G. Abusaada, Abeer M. Elshater (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
This article provides a systematic and critical review of urban paradigms that incorporate economic and cultural diversity, information technology, and competitiveness considering the SDG 11. It explores the possibility of discussing future research using sets of research topics and words of coexistence predefined in urban planning and design literature. This work uses a deductive approach, content analysis and systematic and critical review to highlight the social challenges that address social distancing strategy reflected in SDG 11. The authors systematically focused on blogs published online in 2020, specifically in urban studies, social sciences, planning theory, and public health. They tested their reliability against articles included in the Scimago rank. The findings provide a toolkit with social and behavioural settings, mobility, infrastructure, and urbanization in the post-pandemic era. This study recommended a review of the importance of taking blogs that discuss new urban intellectual models to confront the Coronavirus when developing sustainable cities and societies according to SDG11, after ensuring their reliability.